(untitled) (The Strategic Review for Southern Africa, 2025)
Citizens of Francophone African countries, such as Burkina Faso, Mali and Niger, publicly demonstrated support through civil protests to the military juntas that took over power in these countries. The protesters pressured the juntas to expel French military personnel from the countries. The expulsion of French military and diplomats from these countries is a demonstration of the decline of France’s influence in Francophone Africa. The decline is triggered by a rise in anti-French sentiment across Francophone Africa. Francophone African countries remain the most underdeveloped countries in Africa. The level of underdevelopment has stimulated mal governance which has rendered the struggle for power across Francophone Africa to become intense, to the point that it overshadows the pursuit of democratic stability because of frequent military coups. This chapter, therefore, seeks to answer the following questions; What is the root cause of the decline of French influence in Burkina Faso, Mali and Niger? Why did the public demonstration of anti-French sentiment only take place during the military coups? Were the civilian protests in Burkina Faso, Mali and Niger an expression of pro-coups? Answers to these questions are obtained through an extensive literature review of secondary data that comprise of journal articles, government publications, websites, books and other relevant sources. The study found that because citizens of Burkina Faso, Mali and Niger protested against French military presence in these countries does not mean that they are pro-coups. Anti-French sentiments existed in these countries prior to the recent military coups. The protest, therefore, took place during the military coups because both the juntas and the people had one common aspiration, which is the withdrawal of French military personnel from these countries.